MANAGEMET OF INFEIOR TURBINATE HYPERTROPHY, COMPARISON BETWEEN TRIMMING OF INFERIOR TURBINATES AND SUBMUCOSAL DIATHERMY IN SAME PATIENT - Nassir, Thana Hikmat (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:Background: the inferior turbinate is the largest turbinate & it is variable in size due to changes in its submucosal vascular bed.Aim of study: the aim of the study is the compare between trimming of the inferior turbinate and submucosal diathermy in the same patient a management of turbinate hypertrophy. Subjects